An Investigation of the Relationship between the Biomass Energy Consumption, Economic Growth and Oil Prices - Bildirici, Melike; Ersin, Ozgur (ELSEVIER SCIENCE BV, 2015)
This paper investigates the causality analysis among biomass energy consumption, oil prices and economic growth in Austria, Canada, Germany, Great Britain, Finland, France, Italy, Mexico, Portugal and the U.S. by using the autoregressive distributed lag bounds testing (ARDL) method, Granger causality and Toda and Yamamato non-causality test. The dataset covers the 1970-2013 period. Although many papers have explained the relationship between oil prices and economic growth since 1970, papers have not focused the relationship among biomass energy consumption, oil prices and economic growth. This paper focused the relationship because it was accepted the biomass energy is affected by economic growth and the oil price. For Austria, Germany, Finland and Portugal, the Granger causality test determined the evidence that the conservation hypothesis is supported. In state of U.S., the feedback hypothesis highlights the interdependent relationship between biomass energy consumption and economic growth. Tado Yamamoto test determined, for Austria, Germany, Finland and Portugal, the conservation hypothesis is supported. In state of U.S., the feedback hypothesis highlights the interdependent relationship between biomass energy consumption and economic growth.
Keywords: Economic Growth; Biomass energy; ARDL; VEC; Granger Causality; Toda and Yamamato non-causality test; ELECTRICITY CONSUMPTION; MACROECONOMY; BOUNDS; COINTEGRATION; AUSTRALIA; INFERENCE; DEMAND; OUTPUT; NEXUS; GNP; Business & Economics; Social Sciences - Other Topics